Performance of an irradiated LHCb prototype p-on-n silicon microstrip detector - Bowcock, T; Buytaert, J; Casse, G; Charles, M; Dijkstra, H; Collins, P; Dormond, O; Ferro-Luzzi, M; Fiedler, F; Frei, R; Gagliardi, G; Jalocha, P; et al. (2002)
A prototype silicon detector for the LHCb experiment has been irradiated non-uniformly with fluences of up to 10(15) p/cm(2) of 24 GeV protons and tested with LHC speed electronics in a test beam, After doses equivalent to one year of operation at the LHC, the detector was operational, and deteriorated after higher doses. The performance of this detector identifies particular risks associated with a p-on-n fine pitch design with a double metal layer. (C) 2002 Published by Elsevier Science B.V.